1999
DOI: 10.1093/geront/39.5.546
|View full text |Cite
|
Sign up to set email alerts
|

Educating Nursing Assistants to Communicate More Effectively With Nursing Home Residents With Dementia

Abstract: This article describes the development and evaluation of a Nursing Assistant Communication Skills Program (NACSP). NACSP was designed to help nursing assistants (NAs) interact more effectively with nursing home residents with moderate and severe dementia. In two skilled-care nursing homes, NAs in four units were randomly assigned by unit to NACSP or to a wait-list control condition (UC) and were assessed at baseline, 3 months, and 6 months. NACSP resulted in improvement in the well-being of nursing home reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
211
1
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(218 citation statements)
references
References 26 publications
2
211
1
4
Order By: Relevance
“…[43][44][45][46][47][48][49]52,54,57,61,63,64,66,69,[71][72][73][74][75][76][77][78][79][80][81][82] Costs ranged from £80 to £696 for activities, from £13 to £27 for music therapy, from £3 to £527 for sensory interventions and from £31 to £339 for training and supervising paid caregivers in person-centred care or communication skills, with or without behavioural management training, and DCM. Costs for individual studies are reported alongside the results of the effectiveness review in Tables 1-5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45][46][47][48][49]52,54,57,61,63,64,66,69,[71][72][73][74][75][76][77][78][79][80][81][82] Costs ranged from £80 to £696 for activities, from £13 to £27 for music therapy, from £3 to £527 for sensory interventions and from £31 to £339 for training and supervising paid caregivers in person-centred care or communication skills, with or without behavioural management training, and DCM. Costs for individual studies are reported alongside the results of the effectiveness review in Tables 1-5.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of person-centred care and communication skills and DCM, six studies found the improvements in agitation that persisted up to 6 months beyond the end of the intervention. [75][76][77]79,81,82 In the cost-effectiveness analysis, we limited the time horizon to the time period used to measure outcomes in each study included in the review; where short-and long-term outcomes were reported, we focused on the long-term outcomes. In the cost-utility analysis, given that we found no evidence of effect of interventions beyond 1 year, we limited our time horizon to a 1-year period.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that these employees provide 80% of purchased care for people who have the illness (Mathews 1997;Matteson 1997;McCallion 1999). Regardless of their experience in dementia care, these staff are usually expected to take on the care of patients immediately, hopefully picking up necessary skills on the job or from colleagues and variable training opportunities (Lintern 2000).…”
Section: Clinical Vignette Amentioning
confidence: 99%
“…Key studies on valuing care workers Kihlgren 1990Kihlgren , 1996Williams 1994;Hagen 1995;Matteson 1997;Moniz-Cook 1998;McCallion 1999;Proctor 1999;Wilkinson 1999;Lintern 2000;Wells 2000;Magai 2002;Testad 2005;Davison 2007.…”
Section: Box 1 Three Stages Of Educationmentioning
confidence: 99%
See 1 more Smart Citation